COVID-19: A unique opportunity to improve laboratory capacity for neglected tropical diseases in sub-Saharan Africa - Adeniran, Adebiyi A.; Hamill, Louise Claire; Selby, Richard; Downs, Philip (Frontiers in Tropical Diseases, 2022)
While many public health and university laboratories have become involved in COVID-19 testing during the pandemic, these laboratories now run the risk of being underutilized as COVID-19 testing wanes. This is particularly true of established COVID-19 laboratories in many low- and middle-income countries (LMICs). In this article, we make a case for repurposing many of these laboratories to support control programs for neglected tropical diseases (NTDs) in endemic countries as they contemplate how to strengthen laboratory capacity for all endemic and emerging epidemiological diseases.